EVALUATION OF SCHEDULE AND THRESHOLD BASED INSECTICIDAL APPLICATION STRATEGIES ON CONCENTRATION AND ACTIVE INGREDIENT AGAINST SUCKING PESTS INFESTING OKRA - ZALA, M. B.; A. P. NIKOSHE, A. P. NIKOSHE; BHARPODA, T. M. (The Bioscan, 2016)
In order to evaluate insecticidal applications strategies along with different doses of thiamethoxam 25 WG and dimethoate 30 EC for the control of sucking pests i.e. jassid, aphid and whitefly infesting okra (Abelmoschus esculentus Moench), present investigations were conducted at Anand Agricultural University, Anand during during summer and kharif, 2012. In comparison to dimethoate 30 EC, thiamethoxam 25 WG on concentration base (0.0125%) applied on schedule base (first spray on appearance of the pests and subsequently five sprays at ten days interval) found effective by recording lowest sucking pests population. The higher fruit yield of okra, economics and Net Insecticidal Cost Benefit Ratio (NICBR) was also recorded in the said treatment.